PENGARUH JUMLAH KATALIS ABU CANGKANG TELUR AYAM DAN WAKTU REAKSI GLISEROLISIS PADA PEMBUATAN MONO DAN DIASILGLISEROL (MDAG) DENGAN MENGGUNAKAN CO-SOLVENT TERT-BUTANOL - Margareth Nainggolan, Retno Dian Purba, Mhd. Yusuf Ritonga (Universitas Sumatera Utara, 2014)
Mono and diacylglycerol is one of oil diversification products that its economics value is higher and its market prospect is brighter in this globalization era. The purpose of this research is to produce mono and diacylglycerol from Refined, Bleached, Deodorized Palm Oil by using waste egg shell as catalyst. Waste egg shell was calcined at temperatur 70oC and time 2 hours to forming active CaO as catalyst. Then the process continued with glycerolysis process. Glycerolysis process produced mono and diacylglyserol. Then mono and diacylglycerol was separated by using separator fannel. Then the upper layer was vaporated to separate mono and diacylglycerol from tert-butanol. Effect of various varible process such as amount of catalyst and glycerolysis time was observed in this research. The best result was at temperature 70oC, co-solvent and oil rasio 3:1 (v/b), reaction time 2 hours, and catalyst amount 4% from oil with maksimum purity 68,61%. Mono and diacylglycerol formed in this reasearh is w/o emulsifier with HLB 5,19. The result of this research showed that waste egg shell is suitable to be used as the source of cheap catalyst to produce mono and diacylglycerol.